Late-onset Pompe disease: preliminary results of enzyme replacement therapy - L. P. Smertina; F. I. Ausheva; A. V. Gryaznov; D. A. Svetlakov; L. N. Kolbasin (Нервно-мышечные болезни, 2019)
Pompe disease is an orphan hereditary accumulation disease associated with a deficiency of the lysosomal enzyme alglucosidase alpha. Manifestations of the disease are associated with pathological deposition of glycogen in body tissues as a result of GAA gene mutation and subsequent reduction in the activity of the enzyme alglucosidase alpha or acid maltase. The variety of phenotypic forms and varying degrees of damage to the skeletal and respiratory muscles, cardiomyocytes and internal organs greatly complicates the diagnosis and treatment of patients with Pompe»s disease. This article describes the clinical case of late-onset Pompe disease, which was followed by a course of enzyme replacement therapy, as well as an assessment of the condition before and after treatment and preliminary results.